PRACTICAL IMPLEMENTATION OF THE MODEL OF FORMATION OF CADETS' READINESS TO ENSURE INFORMATION SECURITY IN PROFESSIONAL ACTIVITIES - Dvoretsky, Dmitry; Kolesnikova, Natalia; Makarkina, Oksana; Lagvilava, Kira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The mass introduction of information technologies in the activities of state structures has made it possible to transfer the efficiency of their functioning to a qualitatively new level. Unfortunately, as a means of action, they have characteristic vulnerabilities and can be used not only for good, but also for harm. For the state, as a guarantor of the stability of a civilized society, the issue of ensuring the security of information processing is particularly important. Despite the automation of many information processes, the most vulnerable link in the work of information systems remains a person. A person acts as an operator of information systems and a consumer of information. The entire service process depends on the competence of the operator and the quality of his perception. There are areas of government activity where the cost of error is particularly high. These include ensuring the life and health of citizens, protecting public order and the state system, and ensuring territorial integrity. The specifics of the spheres must be taken into account when ensuring the security of information. This study concerns official activities that are provided by paramilitary groups. Currently, there is a discrepancy in the level of competence of new personnel in the first months of service. The author traces the shortcomings of general and special professional qualities in the field of information security. The purpose of the study is to substantiate certain pedagogical means of forming cadets ' readiness to ensure information security. As forms of theoretical knowledge, we will use the traditional hypothesis and model, as well as functionally distinguishable judgments – problem, assumption, idea and principle. Empirical forms of knowledge will be observation (experimental method) and fixation of facts. To evaluate the effectiveness of the developed pedagogical tools, we use statistical methods: observation (documented and interrogated) and calculation of generalizing indicators. To formulate conclusions, we will use logical methods: building conclusions and argumentation. The approbation of certain pedagogical tools described in this article showed a significant positive trend in terms of competence in information security issues.